2007
DOI: 10.1128/cvi.00244-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Prolactin Promotes Human Secondary Immunoglobulin Response in Human/SCID Mouse Chimeras

Abstract: Recombinant human prolactin (rhPRL) was administered to huPBL-SCID mice to determine its effects on production of human immunoglobulin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Previous studies also showed that peripheral blood B cells secrete higher levels of antibodies following treatment with human prolactin and IL-2 in vitro, in a dose-dependent manner [25,28]. Also, a study of human/SCID mouse showed that human recombinant prolactin can promote increased IgG production in a secondary response [29]. This is not in accordance with our study, as we found no correlation between prolactin and total immunoglobulin levels.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies also showed that peripheral blood B cells secrete higher levels of antibodies following treatment with human prolactin and IL-2 in vitro, in a dose-dependent manner [25,28]. Also, a study of human/SCID mouse showed that human recombinant prolactin can promote increased IgG production in a secondary response [29]. This is not in accordance with our study, as we found no correlation between prolactin and total immunoglobulin levels.…”
Section: Discussioncontrasting
confidence: 78%
“…Although REM sleep might also support adaptive immune functions, the pro-inflammatory endocrine milieu present during SWS (including high levels of GH, prolactin, and aldosterone and nadir levels of cortisol) is optimally suited for promoting APC-T cell interactions. GH, prolactin, and aldosterone are known to support T-cell migration, the release of pro-inflammatory and Th1 cytokines, cell proliferation, and lymphocyte responses to a microbial challenge (43, 45, 48, 117, 126, 286, 355, 362–365, 380, 389, 478, 516, 518, 524, 575, 583, 601). On the other hand, low levels of cortisol during SWS could allow efficient APC-T cell interactions (157, 211, 417, 427, 438).…”
Section: Sleep Effects On Host Defensementioning
confidence: 99%
“…IgG is an immunoglobulin secreted by plasmocyte when mature B cells are differentiated into plasmocytes by antigen stimulation. It is reported that human-derived IgG can be used to assess whether immune function of SCID mouse with hu-PBL engraftment is reconstructed [ 17 , 18 ] and that antigen stimulation promotes human secondary IgG responses in hu-PBL/SCID mouse [ 19 , 20 ]. Interestingly, a significantly positive relationship exists between the appearance of human IgG and tumorigenesis of B-cell lymphoma in the findings of our present study.…”
Section: Discussionmentioning
confidence: 99%